Toward an effective exome-based genetic testing strategy in pediatric dilated cardiomyopathy. (November 2018) - Herkert, Johanna; Abbott, Kristin; Birnie, Erwin; Meems-Veldhuis, Martine; Boven, Ludolf; Benjamins, Marloes; du Marchie Sarvaas, Gideon; Barge-Schaapveld, Daniela; van Tintelen, J; van der Zwaag, Paul; Vos, Yvonne; Sinke, Richard; et al.
Abstract Purpose We evaluated the diagnostic yield in pediatric dilated cardiomyopathy (DCM) of combining exome sequencing (ES)-based targeted analysis and genome-wide copy-number variation (CNV) analysis. Based on our findings, we retrospectively designed an effective approach for genetic testing in pediatric DCM. Methods We identified 95 patients (in 85 families) with pediatric onset of DCM. We initially excluded 13 of these families because they already had a genetic diagnosis, leaving a total of 31 probands for single-nucleotide polymorphism (SNP) array and trio-ES. We used Human Phenotype Ontology (HPO)-based filtering for our data analysis. Results We reached a genetic diagnosis in 15/31 (48.4%) families. ES yielded a diagnosis in 13 probands (13/15; 86.7%), with most variants being found in genes encoding structural cardiomyocyte components. Two large deletions were identified using SNP array. If we had included the 13 excluded families, our estimated yield would have been 54%. Conclusion We propose a standardized, stepwise analysis of (i) well-known cardiomyopathy genes, (ii) CNVs, (iii) all genes assigned to HPO cardiomyopathy, and (iv) if appropriate, genes assigned to other HPO terms. This diagnostic approach yields the highest increase at each subsequent step and reduces analytic effort, cost, the number of variants of unknown clinical significance, and the chance of incidental findings.